Estrategias metodológicas para el desarrollo de las destrezas con criterio de desempeño del bloque curricular numérico del área de matemática en los niños del cuarto año de educación general básica de la escuela fiscal mixta “José Miguel Burneo Burneo”, periodo lectivo 2011-2012, lineamientos propositivos - Chocho Coello, Julia Mercedes (2014)
The present work of investigation is based on the methodological strategies for the development of the skills by criterion of performance of the block curricular numerically of the area of mathematics on the children of the fourth year of General Basic Education of the School "Jose Michael BurneoBurneo" on the school period 2011-2012, for which one worked with the general aim: to contribute to the qualitative improvement of the methodological strategies to develop the skills with criterion of performance of the block curricular Numerically in the students of the Fourth Year of Basic Education of the fiscal mixed School "Jose Michael BurneoBurneo",School period 2011-2012, which served to have a clear idea of the problem, and to be able to come to the conclusion that the methodological strategies yes influence to achieve the development of the skills of the children. For the production of the present work investigation the methods were in use: scientific, deductive, inductive, descriptive, explanatory, interpretive, the technologies that were applied are: the technology of the observation and the survey applied to the teachers, and children of the school, with the purpose of knowing the reasons that provoke the lack of interest for the mathematics in the students. The field investigation developed with a total of 50 pupils of 4to parallel year "A" and "B" of General Basic Education of the School "Jose Michael BurneoBurneo", 5 teachers of the institution, after applying the instruments and analyzing the information we come to the following conclusions:It is possible to observe that a total commitment exists in the education of his pupils / aces, who are conscious with his obligations, in the main they possess a planning adapted to every topic with his respective methodological strategies this way to achieve the development of the skills in the children / aces, in addition one owes to arouse the teachers on the importance of taking part actively with the children to develop a significant learning and to be able like that to manage to reach the maximum school performance in the pupils; To suggest to the Director of the school, that workshops should be planned inside the institution on the different methodological strategies and the suitable utilization of each one of them in the different areas of study for the teachers and like that they could realize his much more entertaining and dynamic classes